AN OVERVIEW OF PHYSICAL ACTIVITY IN ELEMENTARY SCHOOL A BIBLIOMETRIC ANALYSIS - Karisman, Vicki Ahmad; Kuswahyudi, Kuswahyudi; Setiakarnawijaya, Yasep; Taufik, Muhamad Syamsu; Kastrena, Ervan; Solihin, Amril Rahmat; Rahadian, Adi; Ockta, Yovhandra (STKIP Singkawang, 2024)
The study purpose was Our reviews make some unique contributions. First, we identify authors whose publications can serve as benchmarks for the future of researchers, geographic coverage of